(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2002)
The Argentinian narrative discourse of the 70’s, continuing with a tradition, could not help but assimilate and represent, in its different aspects, the profound historical-political changes both in the country and in the world. The Argentinian narrative of the previous decade had opened the space to texts of strong historical-political tension that did not interfere with their practices. In the seventies, “historical density”, on the one hand, and the political radicalization that affected public spaces, on the other, caused literary practice to converge with political practice and both finally shared a common space of enunciation (note).